Colocvii profesionale de vară 2024: transformarea digitală. Experiența utilizatorilor în bibliotecă. Ce au spus participanții? - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2025)
The article analyzes a new edition of the Summer Professional Colloquia, organized by the B.P. Hasdeu Municipal Library (ML) on July 16-17, 2024, focusing on the digital transformation of libraries and user experience. The event brought together over 70 ML staff members and addressed topics such as artificial intelligence in libraries, resource management, and online user preferences. The launch of the Visual Identity Manual and interactive activities like the City Quest “Chișinău SMART” combined technology with urban exploration and were part of the event’s agenda. A survey conducted by the ML’s Monitoring and Evaluation Department, with 48 respondents, highlighted the impact of the colloquia, their strengths, and areas for improvement. The analysis of this survey provides valuable insights for optimizing future editions of the Colloquia and enhancing professional development at the ML.